PENGARUH PARITAS DAN MEDIA KONSELING MASA NIFAS TERHADAP KEMAMPUAN PERAWATAN MANDIRI IBU POST PARTUM DI BPM VIVI SURABAYA - Yunik Windarti; Uke Maharani Dewi (Jurnal Ilmiah Kesehatan, 2018)
In Indonesia Maternal Mortality Rate (MMR) is still high. Various attempts were made by the government to reduce AKI one of them with the implementation of adequate postnatal care. The success of postnatal care is determined by the mother's ability to care for him, especially since birth experience (parity) and the delivery of health information (media counseling) is good. The aim of research to determine the effect of parity and media postnatal counseling on self-care ability of others. postpartum Analytical research design. The population postpartum mothers day 1-10 for 30 people in BPM Vivi in April-June 2017, the sample size of 30 people were taken to the technique of "total sampling". The independent variable parity and media counseling, self-care dependent mothers. postpartum Analysis by Chi squaretest.the results showed that primiparous majority (63.3%) are less able to perform self-care, multipara almost entirely (78.9%), both in performing self-care with p = 0.047. leaflet media health education with the majority ( 60.0%) less than in performing self-care, media counselor almost entirely (86.7%) either do self-treatment with p = 0.023. this study concluded that the higher the better parity self-care during childbirth and direct counseling method (counselor) better than the media leaflets in self-care during childbirth. Therefore for health workers in providing services to clients KIE further improve the media direct counseling.